2013
DOI: 10.1021/jf401827x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Curcumin with Bovine Serum Albumin in the Presence of ι-Carrageenan and Implications on the Stability and Antioxidant Activity of Curcumin

Abstract: This work studied the influences of formation of BSA/ι-carrageenan complexes on the binding, stability, and antioxidant activity of curcumin. In the presence of BSA and ι-carrageenan, curcumin gives higher intensities of absorption and fluorescence than free curcumin and curcumin only combined with BSA. The added ι-carrageenan is observed to promote curcumin for quenching the instrinsic fluorescence of BSA. These results are explained in terms of the formation of BSA/ι-carrageenan complexes, which help to stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 31 publications
10
55
0
1
Order By: Relevance
“…In addition, when Ly and CMC existed in the solutions simultaneously, the intensities of both spectra of Cur strikingly increased. The results indicated that more of Cur was solubilized in Ly solution because there was a hydrophobic microenvironment in Ly, and the Ly-CMC coacervates gave a more hydrophobic region than Ly alone, which agreed well with Yang' report about the BSA/ι-carrageenan complexes to encapsulate Cur (Yang et al, 2013). The largest negative charges of CMC 1.2 produced the largest electrostatic interaction between Ly and CMC.…”
Section: The Uv-vis Absorption and Fluorescence Characterizations Of supporting
confidence: 87%
See 2 more Smart Citations
“…In addition, when Ly and CMC existed in the solutions simultaneously, the intensities of both spectra of Cur strikingly increased. The results indicated that more of Cur was solubilized in Ly solution because there was a hydrophobic microenvironment in Ly, and the Ly-CMC coacervates gave a more hydrophobic region than Ly alone, which agreed well with Yang' report about the BSA/ι-carrageenan complexes to encapsulate Cur (Yang et al, 2013). The largest negative charges of CMC 1.2 produced the largest electrostatic interaction between Ly and CMC.…”
Section: The Uv-vis Absorption and Fluorescence Characterizations Of supporting
confidence: 87%
“…Besides, the maximum spectra of Cur in Ly-Cur-CMC coacervates showed a distinct red shift in absorption spectra and a blue shift in fluorescence spectra, compared with those in free Cur and Ly-Cur solutions. The shifts of peaks also confirmed that the environment around Cur was more hydrophobic (Yang et al, 2013).…”
Section: The Uv-vis Absorption and Fluorescence Characterizations Of mentioning
confidence: 53%
See 1 more Smart Citation
“…A major problem is that curcumin is insoluble in water, which limits its application, and therefore, many methods have been used to overcome this barrier to expand its application. Such methods involve using ionic liquid (Luo, Varaprasad, Reddy, Rajulu, & Zhang, 2012) or sodium phosphate buffer (Yang, Wu, Li, Zhou, & Wang, 2013) or dimethylsulfoxide (Bajpai, Chand, Ahuja, & Roy, 2015b) to dissolve curcumin or turn curcumin into curcumin nanoparticles or liposomal curcumin (Raghavendra, Jayaramudu, Varaprasad, Ramesh, & Raju, 2013). However, these methods are expensive and complex.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in the DSC heating curve, endothermic peaks show intermolecular hydrogen bond breaking, GLP20 changed from triple helix structure is a single irregular coiled conformation, and after cooling reheating process, endothermic peak with the increase in the number of scans becomes small gradually, show that more than 135 DEG C heating caused by the conformational transition is irreversible. Differential scanning calorimetry (DSC) can also be senior structure of composite material, such as the application of the technique to study indicated that with the changes in the environment, carrageenan will conformational transition from helical to random coil form, and combined with macromolecular substances, due to the presence of steric hindrance, it cannot occur normal folding [23]. As a result, the DSC curve is larger endothermic peak as the evaluation of a drug delivery system, carrageenan and poly -(dimethylamino) phosphazene compound is stable is an important index [24].…”
Section: Analysis Of the Advanced Structure Of Polysaccharidementioning
confidence: 99%